2011
DOI: 10.1128/jb.00418-11
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Bacillus anthracis Phosphoglucosamine Mutase, an Enzyme in the Peptidoglycan Biosynthetic Pathway

Abstract: Phosphoglucosamine mutase (PNGM) is an evolutionarily conserved bacterial enzyme that participates in the cytoplasmic steps of peptidoglycan biosynthesis. As peptidoglycan is essential for bacterial survival and is absent in humans, enzymes in this pathway have been the focus of intensive inhibitor design efforts. Many aspects of the structural biology of the peptidoglycan pathway have been elucidated, with the exception of the PNGM structure. We present here the crystal structure of PNGM from the human pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(75 citation statements)
references
References 35 publications
3
72
0
Order By: Relevance
“…This observation is in excellent agreement with previous results (7). Moreover, GlmM exhibited a strong self-interaction, which corresponds to its previously reported formation of homodimers (43). Moreover, we detected a weak but significant interaction between CdaA and GlmM.…”
Section: Resultssupporting
confidence: 54%
“…This observation is in excellent agreement with previous results (7). Moreover, GlmM exhibited a strong self-interaction, which corresponds to its previously reported formation of homodimers (43). Moreover, we detected a weak but significant interaction between CdaA and GlmM.…”
Section: Resultssupporting
confidence: 54%
“…The active site is located in the large central cleft, found at the confluence of the four domains, and is typically positively charged. 20,21,23 As reflected in their sequence conservation, the arrangement of key active-site loops and catalytic residues is highly similar in all of the known structures (Fig. 1b).…”
Section: Resultsmentioning
confidence: 86%
“…Another feature commonly observed in the crystal structures is conformational variability of the C-terminus, which moves via a hinge-type rotation relative to the rest of the protein, and is correlated with ligand binding. 16,18,20,21,25,26 Until recently, the quaternary structures of these proteins had been largely unexamined, perhaps because the best characterized enzymes were known to be monomers. However, biochemical characterization of Salmonella typhimurium PGM (StPGM) and Bacillus anthracis PNGM (BaPNGM) demonstrated that these two proteins exist as dimers in solution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations